Toxicological analysis of acetone in a forensic case for the diagnosis of fulminant type 1 diabetes mellitus (Bangladesh Journal of Medical Science, 2020)
Background: A male in his thirties was found dead in his apartment. On the day before he found dead, he had multiple vague physical complaints, including abdominal pain, vomiting, mouth dryness, and chillness. On autopsy, his liver showed extensive fatty changes, but changes in the other organs were unremarkable.Method: Toxicological analysis showed high concentrations of acetone in his blood (1651 μmol/l) and urine (1913 μmol/l), without any measurable amounts of ethanol.Result: Biochemical analysis indicated high levels of 3-hydroxybutyric acid and acetoacetic acid in the plasma, low levels of plasma C-peptide, and normal levels of hemoglobin A1c. Tests for islet-related antibodies in the plasma yielded negative results. Immunohistological examination indicated selective destruction of the pancreatic islet β cells. Based on these findings, we concluded that the cause of death was fulminant type 1 diabetes mellitus associated with diabetic ketoacidosis.Conclusion: Thus, the toxicological analysis of acetone in the blood and urine is important for the diagnosis of death from fulminant type 1 diabetes mellitus.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.414-419